2017
DOI: 10.1177/1742271x17733146
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography in the pronator quadratus muscle following distal radial fracture fixation: A feasibility study comparing the operated versus nonoperated sides

Abstract: The aim of this study was to assess changes in shear wave velocity within the pronator quadratus muscle in patients following volar plate fixation for distal radial fractures compared to the contralateral nonoperated side. Shear wave velocity values were obtained in the short and long axis of the pronator quadratus muscle, which were analyzed separately. Patients were also stratified by age below or above 66 years. Statistical analysis was performed using paired sample Wilcoxon signed rank and t tests. Pearson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This was thought to be due to fatty infiltration and atrophy leading to less stiffness and a decreased SWV. SWV values may also be useful in the assessment of postop changes in muscle, and this technique may provide the ability to compare with internal controls for rehabilitation monitoring [ 77 ]. Studies have found SWE helpful in evaluating fatty degeneration of muscle and found it to correlate well with results obtained by MRI and conventional ultrasound [ 78 ].…”
Section: Ultrasound Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…This was thought to be due to fatty infiltration and atrophy leading to less stiffness and a decreased SWV. SWV values may also be useful in the assessment of postop changes in muscle, and this technique may provide the ability to compare with internal controls for rehabilitation monitoring [ 77 ]. Studies have found SWE helpful in evaluating fatty degeneration of muscle and found it to correlate well with results obtained by MRI and conventional ultrasound [ 78 ].…”
Section: Ultrasound Elastographymentioning
confidence: 99%
“…When compared with traditional material testing techniques, SWE correlates well when the transducer is parallel to the underlying muscle fibers, highlighting that standardization of elastography protocols is important [ 83 , 118 , 119 ]. SWE has limited depth of penetration, and SWV values also vary by depth and ROI proximity to stiffer materials such as tendon tissues or calcium, so further development of protocols that are consistently followed is important [ 77 ]. Elastography models often assume a linear and purely elastic material; however, biological tissues are typically nonlinear, viscoelastic, and anisotropic [ 120 ].…”
Section: Quantitative Ultrasound Limitations In Skeletal Muscle Evalu...mentioning
confidence: 99%